Under the cover of murder - Elliott, Lauren (Elliott, Lauren. Beyond the Page bookstore mystery., 2021)
"The impending nuptials of Serena Chandler and Zach Ludlow will take place aboard his family's luxurious super-yacht, currently moored in the harbor and the talk of the town. But on the day of the wedding, a man's body washes up on the beach with no ID, only a torn page from a book in his pocket...bibliophile Addie is called in to identify the book, but she cannot. The morning following the extravagant ceremony, a second body washes ashore and Addie has a sinking feeling that the two deaths are connected"--